Developing a Generalized Combined Model for Gas-liquid Two-phase Flow Pressure Drop in Elbow Bends - N.Z Aung; T Yuwono (Universitas Gadjah Mada, 2012)
In this work, a generalized combined model was proposed for prediction of two-phase flow pressure drop in elbow bends. In this proposed model, restriction, frictional and elevational losses were considered separately. The frictional and static losses were approached by using Lockhart_Martinelli correlation. This model was tested to predict the pressure drop across the elbows with inside diameter of 0.036 m and R/D = 0.6, 2.5. The superficial liquid velocity was varied in the range of0.3 1.1 m/s and volumetric gas quality was varied from 0.02 0.3. The results from this model had good predictions with a maximum error of ±13% for long elbow bends and showed great discrepancy with a peak error of –50% for short elbow bends. The model is reliably acceptable for the elbow bends with relative radius (R/D) greater than 2 at volumetric gas fractions less than 0.3.